Quantitative Analysis Reveals Expansion of Human Hematopoietic Repopulating Cells After Short-term Ex Vivo Culture - Bhatia, Mickie (The Rockefeller University Press, 1997)
Ex vivo culture of human hematopoietic cells is a crucial component of many therapeutic applications. Although current culture conditions have been optimized using quantitative in vitro progenitor assays, knowledge of the conditions that permit maintenance of primitive human repopulating cells is lacking. We report that primitive human cells capable of repopulating nonobese diabetic (NOD)/severe combined immunodeficiency (SCID) mice (SCID-repopulating cells; SRC) can be maintained and/or modestly increased after culture of CD34(+)CD38(−) cord blood cells in serum-free conditions. Quantitative analysis demonstrated a 4- and 10-fold increase in the number of CD34(+)CD38(−) cells and colony-forming cells, respectively, as well as a 2- to 4-fold increase in SRC after 4 d of culture. However, after 9 d of culture, all SRC were lost, despite further increases in total cells, CFC content, and CD34(+) cells. These studies indicate that caution must be exercised in extending the duration of ex vivo cultures used for transplantation, and demonstrate the importance of the SRC assay in the development of culture conditions that support primitive cells.